Souffrance des enseignants du secondaire ; accompagnement de neuf enseignants français en demande d’aide - Hélène Veyrac; Agnès Dumas (Perspectives Interdisciplinaires sur le Travail et la Santé)
After providing a brief overview of publications on teachers’ mental stress, we present the implementation of a programme for the guidance and psychological assistance of teachers. This research was based on data collected from the situation of nine teachers who asked for help from this programme. We were then able to: (i) analyze the teachers’ distress as expressed, (ii) describe the main outlines of the support provided, and (iii) relate the outcome of that guidance. The discussion stresses the contribution of such data to research on teachers’ work.